O granicach wolności w wychowaniu. Kilka uwag na marginesie rozprawy Bogdana Nawroczyńskiego Swoboda i przymus w wychowaniu - Dormus, Katarzyna; Włoch, Anna (Biuletyn Historii Wychowania, 2020)
The aim of the article is to present a classic pedagogical concept entitled Freedom and compulsion in education by Bogdan Nawroczyński, an outstanding founder of Polish pedagogy, and to indicate its topicality in the postmodern world. Nawroczyński’s dissertation should be a compulsory reading for students of pedagogy who would have an opportunity to learn about the contribution of this outstanding scientist to the development of Polish pedagogy. Presenting the complexity of the issue of education in the postmodern world in the context of Nawroczyński’s dissertation proves the importance and validity of his concept. The article is mainly based on an analysis of Nawroczyński’s original dissertation, published in 1929, accompanied by the approach of contemporary researchers on the subject of freedom in education.